Determination of iron in solutions containing iron complexes - Tennant, G. B. (1969)
A method of estimating the iron content of solutions containing haemoglobin, ferritin, or ferrioxamine is described. Iron is released by treatment with acid permanganate and ascorbic acid before conventional determination by an Auto Analyzer technique.